Effects of pentobarbital anesthesia on nociceptive processing in the medial and lateral pain pathways in rats - Wang, Ning (Neurosci Bull, 2010)
OBJECTIVE: To investigate the effects of pentobarbital anesthesia on nociceptive processing in the medial and lateral pain pathways. METHODS: Laser stimulation was employed to evoke nociceptive responses in rats under awake or anesthetic conditions. Pain-related neuronal activities were simultaneously recorded from the primary somatosensory cortex (SI), ventral posterolateral thalamus (VPL), anterior cingulate cortex (ACC), and medial dorsal thalamus (MD) with 4 eight-wire microelectrode arrays. RESULTS: Compared with the awake state, pentobarbital anesthesia significantly suppressed the neural activities induced by noxious laser stimulation. Meanwhile, the pain-evoked changes in the neuronal correlations between cortex and thalamus were suppressed in both medial and lateral pain pathways. In addition, the spontaneous firing rates in all the 4 areas were altered (including inhibition and excitation) under the condition of anesthesia. CONCLUSION: The nociceptive processing in the brain can be dramatically changed by anesthesia, which indicates that there are considerable differences in the brain activities between awake and anesthetized states. It is better to employ awake animals for recording neural activity when investigating the sensory coding mechanisms, especially pain coding, in order to obtain data that precisely reflect the physiological state.